First use of 18F-FDG PET in TEMPI syndrome: can it be used for treatment assessment? A case report - Pasquesoone, Henri; Callaud, Aurélien; Carsuzaa, Thibaut; Chalopin, Thomas; Santiago-Ribeiro, Maria-Joao (Frontiers in Nuclear Medicine, 2023)
TEMPI syndrome (TEMPI) compounds telangiectasias and polycythemia with elevated erythropoietin levels, monoclonal gammopathy, perirenal fluid collections, and intrapulmonary shunt. Although the pathophysiology of this syndrome remains unclarified, prior research has been established that it is a plasma cell neoplasm, often containing less than 10% bone marrow plasma cells. 18F-FDG PET serves as a valuable instrument for initial staging and treatment monitoring in multiple myeloma management. Thus, 18F-FDG PET can be legitimately applied for TEMPI assessment. Here, we present the first 18F-FDG PET images for the initial evaluation and treatment monitoring of TEMPI in a 51-year-old woman, who exhibited polycythemia (EPO:5,448 mIU/ml) without JAK2 mutation, telangiectasias, monoclonal IgG lambda gammopathy (13.9) g/L and 7% dysmorphic plasma cells (CD38 + CD138+), occasionally clustered, in favor of tumoral plasmacytomas. The first PET scan exhibited hypermetabolic diffuse bone marrow, potentially related to polycythemia, accompanied by non-lytic bone hypermetabolic lesions in the femoral and humeral diaphysis, and ametabolic peri-renal fluid collections, brown fat, and pleural talcoma. Post-treatment 18F-FDG PET (Daratumumab Bortezomib Thalidomide Dexamethasone) revealed a completely reduced signal of bone lesions, suggesting a complete response, which was substantiated both clinically and biologically, with the concurrent disappearance of telangiectasia and the monoclonal component, and the normalization of the EPO level. In future, additional data will be required to confirm the added value of 18F-FDG PET with TEMPI. Nevertheless, 18F-FDG PET can be a preferred tool for the extension workup and therapeutic evaluation of TEMPI syndrome.